2012
DOI: 10.1136/archdischild-2012-302529
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial balloon occlusion in children with complex pulmonary air leaks

Abstract: Pulmonary air leaks in children are most commonly due to infection or barotrauma. While cases of severe barotrauma are falling because of advances in neonatal care, the incidence of necrotising pneumonia is rising. The majority of air leaks can be managed conservatively, but more severe cases pose a significant challenge to the clinician. The use of occlusive endobronchial balloons is an established anaesthetic technique for a number of indications, but is not widely used in children. We conducted a review ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…The technique has been described in only a few case reports, and for bronchopleural fistula consists of placing a guidewire along the endotracheal tube and a balloon angiography catheter with a small volume of contrast agent [94,116]. Under fluoroscopic guidance the fistula can be detected by inflating the balloon in different sites until the chest tube stops producing bubbles.…”
Section: Balloon Dilation and Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique has been described in only a few case reports, and for bronchopleural fistula consists of placing a guidewire along the endotracheal tube and a balloon angiography catheter with a small volume of contrast agent [94,116]. Under fluoroscopic guidance the fistula can be detected by inflating the balloon in different sites until the chest tube stops producing bubbles.…”
Section: Balloon Dilation and Occlusionmentioning
confidence: 99%
“…The balloon should be deflated at intervals for short periods of time to reduce pressure on the bronchial walls, and care must be taken to avoid balloon overdistension. Potential adverse effects include accumulated secretions with a risk of infection, necrosis, stenosis or bronchial wall erosion with potential migration of the balloon [116]. Balloon occlusion has been detailed in only one paediatric case with life-threatening haemoptysis [94].…”
Section: Balloon Dilation and Occlusionmentioning
confidence: 99%
“…Several techniques have been used to occlude the bronchi, but none have been widely studied. Bronchial occlusion can have complications, such as necrosis, erosion of the bronchial wall or bronchial stenosis, airway perforation, and distal infection [11]. Lewis et al [12] reported one of the first cases of selective bronchial occlusion in a 26-week preterm infant with hyaline membrane disease with a persistent air leak that was successfully treated using a Swan-Ganz catheter.…”
Section: Discussionmentioning
confidence: 99%
“…HATHORN et al [165] reported six patients with complex air leaks treated with endobronchial balloon occlusion. The intervention was successful in two cases of broncho-pleural fistulae and in one of two cases of intra-pulmonary leak.…”
Section: Paediatric Bronchologymentioning
confidence: 99%